Analisis Isi Mengenai Kekerasan Seksual Pada Film Like & Share - Safitri, Nur Aida; Nurlita, Ita (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2025)
ABSTRACT Currently, films have educational capabilities, namely the utilization of films in the world of education. In order to convey messages to audiences, one of the films that has a message that occurs in problems in Indonesia regarding sexual violence is a film entitled